Moraceae diversity in the Universitas Sumatera Utara's arboretum - Arida Susilowati; Deni Elfiati; Ida Mallia Ginting; Muhammad Irvan Rizmi (Talenta Publisher, 2024)
The arboretum of the Universitas Sumatera Utara (USU) is an area for collecting and conserving tree species in North Sumatra. One of dominant family found in USU Arboretum is Moraceae.Â The objective of this reserach was to determine Moraceae diversity in the USU Arboretum. The census approach of vegetation analysis was used to determine the identity and abundance of Moracea. The research found 9 (nine) Moraceae species belongs to two genera in the USU arboretum, those were Ficus microcarpa, Ficus elastic, Artocarpus heterophyllus, Ficus padana, Ficus fistulosa, Artocarpus altilis, Ficus benjamina, Ficus ampelas and Ficus hispida. The species with the highest density value (57.92%) is Ficus hispida. The diversity index, richness index, and species dominance index were all quite low in the research location, with values of 1.455, 1.226, and 0.370, respectively. Meanwhile, the species evenness index at the research location is 0.662, which is classified into moderate. To improve the diversity of Moraceae in the USU arboretum, species enrichment activities are needed.